2016
DOI: 10.1139/cjpp-2015-0242
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone and exenatide enhance cognition and downregulate hippocampal beta amyloid oligomer and microglia expression in insulin-resistant rats

Abstract: Insulin resistance is known to be a risk factor for cognitive impairment, most likely linked to insulin signaling, microglia overactivation, and beta amyloid (Aβ) deposition in the brain. Exenatide, a long lasting glucagon-like peptide-1 (GLP-1) analogue, enhances insulin signaling and shows neuroprotective properties. Pioglitazone, a peroxisome proliferated-activated receptor-γ (PPAR-γ) agonist, was previously reported to enhance cognition through its effect on Aβ accumulation and clearance. In the present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 70 publications
0
21
0
1
Order By: Relevance
“…Furthermore, thiazolidinedione drugs are insulin sensitizers and deficits in the insulin pathway are co-morbid with cognitive impairment in AD (Gad et al, 2015; Sato et al, 2011; Perez & Quintanilla, 2015; Rodriguez-Rivera et al, 2011; Jahrling et al, 2014; Xu et al, 2014; Cowley et al, 2012; Bosco et al, 2011; Escribano et al, 2010; Escribano et al, 2009). Based on this evidence, we posited that genetic deletion of FGF14 could affect the insulin pathway.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, thiazolidinedione drugs are insulin sensitizers and deficits in the insulin pathway are co-morbid with cognitive impairment in AD (Gad et al, 2015; Sato et al, 2011; Perez & Quintanilla, 2015; Rodriguez-Rivera et al, 2011; Jahrling et al, 2014; Xu et al, 2014; Cowley et al, 2012; Bosco et al, 2011; Escribano et al, 2010; Escribano et al, 2009). Based on this evidence, we posited that genetic deletion of FGF14 could affect the insulin pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Epidemiological studies have demonstrated a link between insulin signaling, cognition, and risk for AD. Supporting this link, the class of insulin-sensitizing drug known as the thiazolidinediones, which includes rosiglitazone (RSG) and pioglitazone (PIO), and are potent and selective agonist of the peroxisome proliferator-activated receptor gamma (PPARγ), has shown efficacy in patients with MCI (Mild Cognitive Impairment) and concomitant insulin resistance (Risner et al, 2006; Harrington et al, 2007; Watson et al, 2005; Gad et al, 2015; Sato et al, 2011; Perez & Quintanilla, 2015). Likewise, RSG treatment rescues hippocampus-dependent cognitive function in the Tg2576 AD mouse model (Rodriguez-Rivera et al, 2011; Denner et al, 2012) by a mechanism that involves normalized intrinsic excitability and synaptic function of granule neurons in the dentate gyrus (DG), a critical location for new memory formation (Nenov et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the blockade of PPARα and PPARβ/δ may be impairing the formation of a new memory upon reexposure to the conditioned arena. Most studies investigating the role of PPARs in memory have investigated their role in models of mnemonic impairment, such as diabetes-induced cognitive dysfunction [35,36], morphine-induced mnemonic dysfunction [13], scopolamine-induced memory…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the blockade of PPARα and PPARβ/δ may be impairing the formation of a new memory upon re-exposure to the conditioned arena. Most studies investigating the role of PPARs in memory have investigated their role in models of mnemonic impairment, such as diabetes-induced cognitive dysfunction [35,36], morphine-induced mnemonic dysfunction [13], scopolamine-induced memory impairment [37][38][39] and others [40][41][42][43]. There are studies showing that the modulation of PPARs may also affect memory in subjects whose mnemonic abilities were preserved.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies indicate that in patients with cognitive impairment or AD in early stages, thiazolidinediones improve long‐term memory functioning (Galimberti & Scarpini, ) . Also, in murine models, it is evident that the treatment with this drug improves synaptic transmission and reduces neuronal damage, in response to a toxicity (Gad, Zaitone, & Moustafa, ). However, further studies are needed to demonstrate that thiazolidinediones are one more option for the treatment of AD.…”
Section: Alzheimer Diseasementioning
confidence: 99%